Mechanisms of Cancer Inhibition by Local Anesthetics - Zhang, Yiguo; Jing, Yixin; Pan, Rui; Ding, Ke; Chen, Rong; Meng, Qingtao (Frontiers in Pharmacology, 2021)
The use of local anesthetics during surgical treatment of cancer patients is an important part of perioperative analgesia. In recent years, it has been showed that local anesthetics can directly or indirectly affect the progression of tumors. In vitro and in vivo studies have demonstrated that local anesthetics reduced cancer recurrence. The etiology of this effect is likely multifactorial. Numerous mechanisms were proposed based on the local anesthetic used and the type of cancer. Mechanisms center on NaV1.5 channels, Ras homolog gene family member A, cell cycle, endothelial growth factor receptor, calcium Influx, microRNA and mitochondrial, in combination with hyperthermia and transient receptor potential melastatin 7 channels. Local anesthetics significantly decrease the proliferation of cancers, including ovarian, breast, prostate, thyroid, colon, glioma, and histiocytic lymphoma cell cancers, by activating cell death signaling and decreasing survival pathways. We also summarized clinical evidence and randomized trial data to confirm that local anesthetics inhibited tumor progression.